Comparison of Effects of Intravenous Lignocaine and Magnesium Sulphate on the Cardiovascular Response to Laryngoscopy and Intubation - Roheena Wadud, Muhammad Haseeb Moin Ud Din Baloch, Imran Ul Haq, Muhammad Kamran Khan, Khayyam Farid, Tanzeela Firdous, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Objective: The patient's heart rate, blood pressure, pulmonary arterial pressure, and capillary wedge pressure will all rise during laryngoscopy and tracheal intubation. These hemodynamic alterations are less noticeable in those with normal blood pressure but have been linked to several diseases. They are well tolerated by those with normal blood pressure. The study's goal is to compare the cardiovascular effects of lignocaine and magnesium sulfate during laryngoscopy and intubation. Methodology: The objective of this randomized controlled trial was to examine the effects of lignocaine and magnesium sulfate on cardiovascular and respiratory responses after endotracheal intubation in ASA I patients. The 60 participants' ages ranged from 15 to 45, and they were all classed as "grade I" by the ASA. Each of these patients underwent elective surgery under general anesthesia voluntarily. The sixty people were divided into two groups of thirty using a random selection method. Neither group was significantly different from the other in terms of demographics or blood-flow parameters. Group L was administered 1.5 mg/kg intravenously of lidocaine three minutes before to induction. Group M received an intravenous injection of magnesium sulfate at a rate of 40 mg/kg over the course of one minute. Results: In both the Magnesium and Lignocaine groups, heart rates increased, but the Lignocaine group's increase was far more dramatic (p value 0.01). Both groups experienced an increase in systolic blood pressure following medication administration (p value 0.05). The results of Group M remained statistically significant for the first minute after the insertion of the tube, but by the fifth minute, they had returned to pre-insertion levels. In Group L, blood pressure increased significantly at 1 and 3 minutes after tube insertion, but by 5 minutes, blood pressure had returned to pre-insertion levels. The SBP of group L individuals increased significantly greater than that of group M participants. (p 0.05). Immediately following intubation, there was a statistically significant (p 0.01) increase in DBP in both groups; however, three minutes later, DBP had returned to pre-intubation levels in both groups (p 0.01). It is five percent as important. (p 0.05). The results revealed that the growth rate of group L members was significantly higher than that of group M members. In the presented situation, p equals 0.01 Conclusion: When it comes to preventing a rise in heart rate, blood pressure, and blood pressure during laryngoscopy and tracheal intubation for patients with an ASA grade I, magnesium sulfate is more beneficial than lidocaine.